Amphibians occurring in soybean and implications for biological control in Argentina - Attademo, Andres Maximiliano (2005)
The diversity and diet composition of amphibians were examined in soybean of the Córdoba and Entre Ríos Provinces of Argentina, investigating their potential as biological control agents of herbivores species. A total of 15 anuran species belonging to three families were detected in the two crops. The numbers of individuals found in soybean and the variety of arthropods they consumed suggest that anuran populations could be important biological control factors of soybean arthropods.